The Sheng Identity, Cultural Background and Their Influence on Communication in Academic Endevours: The Case of Machakos University College - Mmbwanga, Florence; Etakwa, Everlyn (International Journal of Social Science and Economics Invention, 2016)
Young people in Kenya want to be identified with Sheng and some, in addition, want to be identified with their cultures. Sheng is a slang language originating in Nairobi, Kenya, spoken by the youth all over the country. It is a mixture of several languages, mainly English, Kiswahili and Kenyan languages. It is coined in the eastern part of the city. Youths from other parts of the country also come up with their own vocabulary which may be at variance with this Sheng. At Machakos University College there are various types of Sheng used which become a hindrance in the communication process between the students themselves and in academic discourse.Cultural background, which is manifested in incorrect pronunciations, coupled with dissimilar interpretations of the varieties of sheng also affects communication in academic discourse.The objectives of this study are designed to answer the quest ion of whether the use of Sheng and the cultural background of the students have an impact on communication between the lecturer and the students and among students themselves.Purposive sampling will be used to get the respondents. Qualitative methods will be used to analyze the data. The findings of the study will be used to come up with a way of mitigating so as to improve communication in academic discourse.In conclusion, this study purposes to establish the fact that it’s not just Sheng but the various types of Sheng used and that each individual wants to identify with their type, so these types can affect communication in academic discourse. The potential impact of conducting this research is to improve communication in academic discourse